Enhanced Antibacterial Properties of Polyester and Polyacrylonitrile Fabrics Using Ag-NP Dispersion/Microwave Treatment. Issue 2 (March 2014) - Ibrahim, N. A.; Kadry, G. A.; Eid, B. M.; Ibrahim, H. M.
A Ag-nanoparticle (Ag-NP) dispersion was successfully synthesized using a glucose/Ag-nitrate/polyvinyl pyrrolidone (PVP)/sodium hydroxide reduction formulation. The resultant Ag-NP dispersion was successfully used alone and in combination with Disperse Orange 31 or Basic Blue 9 dyes to impart antibacterial properties against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria to polyester and polyacrylonitrile fabrics respectively using microwave treatment. An increase in Ag-NP dispersion concentration by 50% and prolonged microwave irradiation by two minutes significantly improved the antibacterial performance. The EDX spectrum of the Ag-NP loaded substrates confirmed the presence of elemental Ag (Ag 0 ) on the fabrics' surface. Addition of selected disperse or basic dye to the Ag-NP treatment bath produced disperse or basic dyeings with darker depth of shades and remarkable antibacterial functionality.